The United Nations Framework Convention on Climate Change: orchestration as a governance mode - Garcia, Miriam Lia Cangussu Tomaz (2021)
Even if States are the central actors, this research is based on the premise that facing climate change requires the participation of subnational governments and non-state actors. Over the past few years, the landscape of global climate governance has changed with the participation of non-state and sub-national actors which are also called non-Party stakeholders. There is also a growing recognition of the role of non-Party stakeholders as implementers of climate actions that are complementary to the national commitments. Non-Party stakeholders can voluntarily pledge for climate commitments both individually and collectively as members of cooperative initiatives. Such pledges are recognized and promoted by the intergovernmental sphere in a governance mode called orchestration. This study focuses on the case of the Lima-Paris Action Agenda, an initiative led by the United Nations Secretary-General Office, the United Nations Framework Convention on Climate Change Secretariat, and the presidencies of the Conference of Parties 20 and 21, led respectively by the governments of Peru and France. The Lima-Paris Action Agenda was established as one of the pillars of the Conference of Parties 21. One of the Lima-Paris Action Agenda main objectives was to demonstrate the engagement of non-Party stakeholders by bringing together cooperative initiatives with ambitious climate commitments in terms of mitigation and adaptation impact. Based on the collection of primary data, this study reconstructs the emergence and operationalization of the Lima-Paris Action Agenda towards COP-21. Then, the research argues that the Lima-Paris Action Agenda catalyzed the institutionalization of orchestration as one of the governance modes of the United Nations Framework Convention on Climate Change Secretariat for the implementation phase of the Paris Agreement. In addition, the thesis presents an analysis of the performance and accountability mechanisms of the Lima-Paris Action Agenda initiatives. This research contributions to the global environmental governance literature are threefold. First, the thesis investigates the conditions that allowed the rapprochement between the intergovernmental sphere and the transnational sphere. Second, the study discusses orchestration as one of the governance modes employed by intergovernmental organizations. The third contribution is an analytical framework for assessing governance structures and accountability mechanisms for cooperative initiatives.